Impact on the recall rate of digital breast tomosynthesis as an adjunct to digital mammography in the screening setting. A double reading experience and review of the literature. Issue 4 (April 2016) - Carbonaro, Luca A.; Di Leo, Giovanni; Clauser, Paola; Trimboli, Rubina M.; Verardi, Nicola; Fedeli, Maria P.; Girometti, Rossano; Tafà, Alfredo; Bruscoli, Paola; Saguatti, Gianni; Bazzocchi, Massimo; Sardanelli, Francesco
Abstract: Objectives: To estimate the impact on recall rate (RR) of digital breast tomosynthesis (DBT) associated with digital mammography (DM + DBT), compared to DM alone, evaluate the impact of double reading (DR) and review the literature. Methods: Ethics committees approved this multicenter study. Patients gave informed consent. Women recalled from population-based screening reading were included. Reference standard was histology and/or ≥1 year follow up. Negative multiple assessment was considered for patients lost at follow up. Two blinded readers (R1, R2) evaluated first DM and subsequently DM + DBT. RR, sensitivity, specificity, accuracy, positive and negative predictive values (PPV, NPV), were calculated for R1, R2, and DR. Cohen κ and χ 2 were used for R1-R2 agreement and RR related to breast density. Results: We included 280 cases (41 malignancies, 66 benign lesions, and 173 negative examinations). The RR reduction was 43% (R1), 58% (R2), 43% (DR). Sensitivity, specificity, accuracy, PPV and NPV were: 93%, 67%, 71%, 33%, 98% for R1; 88%, 73%, 75%, 36%, 97% for R2; 98%, 55%, 61%, 27%, 99% for DR. The agreement was higher for DM + DBT ( κ =0.459 versus κ =0.234). Reduction in RR was independent from breast density ( p  = 0.992). Conclusion: DBT was confirmed to reduce RR, as shown by 13 of 15 previous studies (reported reduction 6–82%, median 31%). This reduction is confirmed when using DR. DBT allows an increased inter-reader agreement.